Lucretian Puzzles - Michael Rabenberg (Ergo, An Open Access Journal of Philosophy)
It seems that people typically prefer dying later to dying earlier. It also seems that people typically do not prefer having been created earlier to having been created later. Lucretius’ Puzzle is the question whether anything typically rationally recommends having a preference for dying later to dying earlier over having a preference for having been created earlier to having been created later. In this paper, I distinguish among three ways in which Lucretius’ Puzzle can be understood and say how I think they ought to be answered.